RESTORATION OF LOST NATURAL LANDSCAPES AND FORMATION OF LOCAL UNDISTURBED ECOSYSTEMS A CASE STUDY OF RECREATIONAL ZONES CONSTRUCTION IN KYIV - Сонько, Сергій; Зеленчук, Іван (SWorldJournal, 2024)
The article explores the challenges of restoring natural landscapes and subsequently forming local undisturbed ecosystems, using the example of recreational zone development in rapidly growing urban agglomerations. The effectiveness of the interaction be